Assessing health care disparities in US organ procurement organizations - Wenbo Wu; Joseph M. Messana; Nicholas Hartman; Lonnie Barnes; Randall S. Sung; Tempie Shearon; Abhijit Naik; John C. Magee; Jonathan Segal; Claudia Dahlerus; Robin Padilla; Ashley Eckard; et al. (Scientific Reports)
Abstract There is extensive system-wide evidence of disparities in access to organ transplantation in the US based on race, ethnicity, and socioeconomic status. However, little information is available regarding care disparities among US organ procurement organizations (OPOs). Commissioned by the US Centers for Medicare and Medicaid Services (CMS), we studied racial/ethnic disparities in organ donation and transplantation across and within OPOs. Based on the 2020 CMS final rule, we calculated OPO donation and organ transplantation rates with 95% confidence intervals for racial (Black, White, and Asian American and Pacific Islander, AAPI) and ethnic (Hispanic and non-Hispanic) groups. OPOs were ranked with national rates as references and classified according to the CMS 3-tier system. Of the 58 OPOs, 8 and 4 had donation rates lower for Black and AAPI donors than for White donors; 21 and 18 had organ transplantation rates lower for Black and AAPI donors than for White donors; 1 and 1 had a donation rate or organ transplantation rate lower for Hispanic donors than for non-Hispanic donors. Significant racial/ethnic disparities in organ donation and transplantation exist among many OPOs, whereas the overall OPO performance is dominated by White and non-Hispanic donors. These disparities may be influenced by variations and structural barriers in resource access, donor identification, transplantation referral, and waitlisting processes–some of which lie partially outside the direct control of OPOs and disproportionately affect disadvantaged populations. Results support equitable organ donation and allocation through enhanced awareness of health care disparities, increased accountability of OPOs, and informed policies and interventions.